2015
DOI: 10.1371/journal.pone.0129050
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Simulation of Flow-Induced Noise in High Pressure Reducing Valve

Abstract: The main objective of this paper is to study the characteristics of flow-induced noise in high pressure reducing valve (HPRV) and to provide some guidance for noise control. Based on computational fluid dynamics (CFD), numerical method was used to compute flow field. Ffowcs Williams and Hawkings Model was applied to obtain acoustic signals. The unsteady flow field shows that noise sources are located at the bottom of plug for valve without perforated plate, and noise sources are behind the plate for valve with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 28 publications
(23 reference statements)
0
13
0
Order By: Relevance
“…Although a reducing valve beside the meter has no substantial influence on measurement, there is a slight tendency to both negative and positive errors (Figure 2e). Flow distortions caused by this type of valve are usually small on the upstream side of the pipe, as has been shown in a numerical simulation (Wei et al, 2015).…”
Section: Woltman Metersmentioning
confidence: 61%
See 1 more Smart Citation
“…Although a reducing valve beside the meter has no substantial influence on measurement, there is a slight tendency to both negative and positive errors (Figure 2e). Flow distortions caused by this type of valve are usually small on the upstream side of the pipe, as has been shown in a numerical simulation (Wei et al, 2015).…”
Section: Woltman Metersmentioning
confidence: 61%
“…The reducing valve causes very small measurement errors, close to those obtained in an installation of straight pipe lengths (Figure 5e), due to the valve being downstream of the meter and, thus, not considerably distorting the meter's inlet flow. In a numerical simulation, this type of valve has been shown not to cause important upstream distortions (Wei et al, 2015).…”
Section: Tangential Metermentioning
confidence: 94%
“…4 Many measures and causes concerning the suppression and elimination of flow-induced noise have been carried out. Wei et al 5 studied the aerodynamic noise in the control valve with a perforated plate. Results are shown that the perforated plate affects the distribution of noise source, and the noise is changed profoundly under the different pressure difference.…”
Section: Introductionmentioning
confidence: 99%
“…(4) Study on the vibration and noise of structure in the valve. Wei et al (2015), Yu J.P. and Yu S.R. (2015) have studied the noise induced by fluctuations in the valve closing pressure.…”
Section: Introductionmentioning
confidence: 99%